The Myths and Local Wisdom as The Enhancment Effort for Positive Image of Tourism Village. - Muhammad Fadli Muslimin (Universitas Muhammadiyah Ponorogo, 2020)
The purpose of the research was to investigate the myths and local wisdom that were developing in Widodomartanii Yogyakarta as well as the continuity effect upon the positive image of the village, and empowered sector to preserve the tourism object. The research subject determined by the information based on the assigned criterion related to potential tourism and its development. The data found considered as ethnographic. Descriptive research conducted on this paper that aims to picture the state of the object of research recent based on the factual data found objectively in the village through field survey. The data collection gathered through three steps. The first was an observation which divided into two. The first was a direct observation in use to gather information about Blue Lagoon. The second was recording observation including recording narrative method; The second was through the interview with MR.Suhadi as the successor of the water management of Blue Lagoon and the others with structured an unstructured interview method; And the third was to filter from related literature. Furthermore, the technique analysis from the gathered information data. The research result found that the myth and the local wisdom in a village organized locally and fully supported can transform an ordinary village turn to be a tourist village so the village can change the image of the previous as ordinary village to tourism village in Widodomartani Village. It also can generally open wider opportunities for the resident to have new beneficial activities.